Answer:
![\textsf{(c)}\quad y=(5-3x)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/f6p7jq6uju1lnkypib46dwswj7b7msz837.png)
Explanation:
To make y the subject of the equation 3x + 4y = 5, use algebraic operations to rearrange the equation and isolate y.
Begin by subtracting 3x from both sides of the equation:
![\begin{aligned}3x+4y-3x&=5-3x\\\\4y&=5-3x\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/ivmwcddzgqgpavpb2029swpxnmgj59xvu7.png)
Now, divide both sides of the equation by 4:
![\begin{aligned}(4y)/(4)&=(5-3x)/(4)\\\\y&=(5-3x)/(4)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/hgl71jdikburt4h5wq4p8mjdzd8stp3fm6.png)
Therefore, the equation is:
![\Large\boxed{\boxed{y=(5-3x)/(4)}}](https://img.qammunity.org/2023/formulas/mathematics/college/iwdprbusjhage1gacvgjdlvpwodc9f3l0f.png)